[1] First, remember that the sum of the angles in a triangle must add up to 180*.
[2] We are told two of the angles, 44* and 66*, but we are missing the third.
[3] Combining [1] and [2], we know that 44* + 66* + ? = 180*. In other words,
110* + ? = 180*
so,
? = 70*
The missing angle 3 is equal to 70 degrees.
The estimated number of lines of code written by computer programmers per hour when x people are working & the correct option is y = 27x - 4.
Table showing the estimated number of lines of code written by computer programmers per hour when x people are working & option given y= 47 * 1.191ˣ y= 34 * 1.204ˣ y=26.9x - 1.3 y = 27x - 4
To Choose the model which best represents the data.
<h3>What is choosing the best model data?</h3>
To understand a set of data, it is helpful to organize it and provide summary descriptions of the set.
People Working lines of code
2 50
4 110
6 160
8 210
10 270
12 320
x y= 47 * 1.191ˣ y= 34 * 1.204ˣ y=26.9x - 1.3 y = 27x - 4
2 66.66 49.3 52.5 50
4 94.57 71.44 106.3 104
6 134.14 103.57 160.1 158
8 190.27 150.14 213.9 212
10 269.91 217.64 267.7 266
12 382.85 315.5 321.5 320.
Below 2 0 4 1
on line 0 0 0 2
Above 4 6 2 3
Therefore y = 27x - 4 is the best fit
To learn more about the scatterplot visit:
brainly.com/question/26270713
The solutions of the equation 3x - y = 1 are (-2,-7),(-1,-4) and (3,8) thus option (A),(B) and (D) are correct.
<h3>What is the equation?</h3>
There are many different ways to define an equation. The definition of an equation in algebra is a mathematical statement that demonstrates the equality of 2 mathematical expressions.
In another word, the equation must be constrained with some constraints.
As per the given equation,
3x - y = 1
Substitute, x = -2
3(-2) - y = 1
y = -7 thus (-2,-7) satisfied.
Similarly (-1,-4) and (3,8) are also satisfied.
Hence "The solutions of the equation 3x - y = 1 are (-2,-7),(-1,-4) and (3,8)".
For more about the equation,
brainly.com/question/10413253
#SPJ1
Step-by-step explanation:
the question is not correct
edit it and I will answer u in comments
Answer:
![\frac{ { \sin}^{2} y}{ { \sec}^{2}y - 1 } = { \cos }^{2} y](https://tex.z-dn.net/?f=%20%5Cfrac%7B%20%7B%20%5Csin%7D%5E%7B2%7D%20y%7D%7B%20%7B%20%5Csec%7D%5E%7B2%7Dy%20-%201%20%7D%20%20%3D%20%20%7B%20%5Ccos%20%7D%5E%7B2%7D%20y)
Step-by-step explanation:
We know that ![{ \tan }^{2} y = { \sec }^{2} y - 1](https://tex.z-dn.net/?f=%20%7B%20%5Ctan%20%7D%5E%7B2%7D%20y%20%3D%20%20%7B%20%5Csec%20%7D%5E%7B2%7D%20y%20-%201)
Also , ![{ \tan}^{2} y = \frac{ { \sin }^{2} y}{ { \cos }^{2}y }](https://tex.z-dn.net/?f=%20%7B%20%5Ctan%7D%5E%7B2%7D%20y%20%3D%20%20%20%5Cfrac%7B%20%7B%20%5Csin%20%7D%5E%7B2%7D%20y%7D%7B%20%7B%20%5Ccos%20%7D%5E%7B2%7Dy%20%7D%20%20)
So ,
![\frac{ { \sin }^{2}y }{ { \sec }^{2}y - 1 } = \frac{ { \sin}^{2} y}{ { \tan }^{2} y} = \frac{ { \sin }^{2}y }{ \frac{ { \sin}^{2} y}{ { \cos}^{2}y } } = { \cos }^{2} y](https://tex.z-dn.net/?f=%20%5Cfrac%7B%20%7B%20%5Csin%20%7D%5E%7B2%7Dy%20%7D%7B%20%7B%20%5Csec%20%7D%5E%7B2%7Dy%20-%201%20%7D%20%20%3D%20%20%5Cfrac%7B%20%7B%20%5Csin%7D%5E%7B2%7D%20y%7D%7B%20%7B%20%5Ctan%20%7D%5E%7B2%7D%20y%7D%20%20%3D%20%20%5Cfrac%7B%20%7B%20%5Csin%20%7D%5E%7B2%7Dy%20%7D%7B%20%5Cfrac%7B%20%7B%20%5Csin%7D%5E%7B2%7D%20y%7D%7B%20%7B%20%5Ccos%7D%5E%7B2%7Dy%20%7D%20%7D%20%20%3D%20%20%7B%20%5Ccos%20%7D%5E%7B2%7D%20y)